2014
DOI: 10.1093/cid/ciu027
|View full text |Cite
|
Sign up to set email alerts
|

DALI: Defining Antibiotic Levels in Intensive Care Unit Patients: Are Current  -Lactam Antibiotic Doses Sufficient for Critically Ill Patients?

Abstract: Infected critically ill patients may have adverse outcomes as a result of inadeqaute antibiotic exposure; a paradigm change to more personalized antibiotic dosing may be necessary to improve outcomes for these most seriously ill patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
706
9
18

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 893 publications
(782 citation statements)
references
References 30 publications
21
706
9
18
Order By: Relevance
“…These would be clinical messages that would further enhance our understanding of this area, although de Montmollin and colleagues have provided important data to help direct further research in this area. In the context of similar recent data from other antibiotics [5,6], this problem should not be considered restricted to aminoglycosides. Indeed, quantification of the clinical advantages of an individualized approach to dosing is urgently required.…”
Section: Why Is This Study Important Controversial and Thought-provomentioning
confidence: 99%
“…These would be clinical messages that would further enhance our understanding of this area, although de Montmollin and colleagues have provided important data to help direct further research in this area. In the context of similar recent data from other antibiotics [5,6], this problem should not be considered restricted to aminoglycosides. Indeed, quantification of the clinical advantages of an individualized approach to dosing is urgently required.…”
Section: Why Is This Study Important Controversial and Thought-provomentioning
confidence: 99%
“…fT>MIC) associated with positive clinical outcomes for β-lactams in critically ill patients is a fT>MIC between 50% to 100% of the dosing interval. 3 Recent studies reported the PK/PD efficacy index for the β-lactamase inhibitor (BLI) tazobactam to be the percentage of time during which the unbound concentration remains above a threshold concentration (fT>CT). 4,5 fT>CT targets ranged from 35 to 85% of the dosing interval, depending on the antibiotic-BLI combination and stability of the β-lactamase.…”
Section: Introductionmentioning
confidence: 99%
“…In selected cases, generally in immunocompromised patients or patients with previous exposure to oseltamivir, there is a higher risk for antiviral resistance; in case of refractory influenza A infection which persists despite neuraminidase inhibitors treatment, a study to assess virus resistance for oseltamivir should be performed and zanamivir should be initiated. It was observed that ICU patient might need an adjustment of the dose of antibiotic because of a different pharmacokinetic and pharmacodynamics; despite that, it seems not to be the case when enteral oseltamivir treatment is initiated [20]; in a study performed in ICU patients with pH1N1 infection, enteral absorption and plasmatic levels of Oseltamivir were therapeutic when a dose of 75 mg twice daily was delivered [21].…”
mentioning
confidence: 99%